Teacher training and professional profile as drivers of quality in higher education - Camargo Romero, Gilma E.; Marín-González, Freddy; Rani Moganadas, Sharmila (Revista de Ciencias Sociales, 2026)
Drawing on theoretical, conceptual, and empirical foundations from university institutional management, this article examines teacher training and the professional profile as key drivers of quality processes in the context of higher education. A mixed-methods study was conducted using a non-experimental, cross-sectional design, integrating quantitative analysis with qualitative evidence derived from observation, participant interaction, and document analysis. The Perception Questionnaire on Teacher Training and Professional Profile, consisting of 22 Likert-scale items, was administered to a purposive sample of 284 university faculty members. The results indicated overall favorable evaluations across the assessed dimensions, with mean scores above 3.8. Exploratory factor analysis confirmed a coherent two-dimensional structure and high levels of internal consistency. However, gaps were identified in areas related to the strengthening of digital competencies, formative assessment, and systematic feedback. The findings indicate that the consolidation of continuous professional development programs aligned with standards of the teaching professional profile contributes to improving the quality of university education.